PENGARUH PEMBERDAYAAN KERJA DAN MOTIVASI TERHADAP KEPUASAAN KERJA DOSEN TETAP PERGURUAN TINGGI SWASTA (STUDI PADA STIE TOTAL WIN SEMARANG) (Students' Journal of Economic and Management, 2015)
This study aims to examine and analyze the effect of empowerment and motivationto job satisfaction STIE TOTAL WIN Semarang. The test data used in this study include product moment test validity, reliability testing with Alpha Cronbrach, multiple linear regression analysis, t test to test and prove the research hypothesis. Data collected tested for validity and reliability analysis method is tested with product moment coefficient alpha (Alpha Cronbrach), in which the results of all the data is valid and reliable. The results of the analysis and discussion indicate that: (1). Empowerment work and significant positive effect on employee job satisfaction, the stronger the effect of empowerment work, then the employee job satisfaction also increased; (2). Work motivation positive and significant impact on job satisfaction, the stronger the influence of work motivation, it also increases employee satisfaction. Keywords: job empowerment, motivation, job satisfaction.